2017
DOI: 10.2141/jpsa.0160060
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Morphology of the Skeletal Forelimb, Pectoral Girdle, and Sternum in Japanese Native Domestic Fowls

Abstract: This study aims to understand the relationships among morphological characteristics, their functional roles, and breeder preferences in Japanese native fowls. We analyzed and compared the shapes and sizes of the skeletal forelimb, pectoral girdle, and sternum among six breeds: Chabo, Oh-Shamo, Onagadori, Shokoku, Tosajidori, and Totenko. Because skeletal forelimb, pectoral girdle, and sternum are one of the bases for composing body appearance and for movement of birds such as flapping, we treated those skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The traditional breeders also believe that in the spiritual world, the appearance of their chicken can be given a fantasy image of aggressiveness, masculinity, and dignity to fascinate cockfighting viewers, although these ambiguous aims of selection are not objective. Because these complicated needs determined the distribution of muscle mass in fighting cocks (Kudo et al, 2017 ), their body size and shape are morphologically distinguished from those of the meat and layer breeds as confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The traditional breeders also believe that in the spiritual world, the appearance of their chicken can be given a fantasy image of aggressiveness, masculinity, and dignity to fascinate cockfighting viewers, although these ambiguous aims of selection are not objective. Because these complicated needs determined the distribution of muscle mass in fighting cocks (Kudo et al, 2017 ), their body size and shape are morphologically distinguished from those of the meat and layer breeds as confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 82%
“…The large fighting cocks (Japanese Shamo and Thai fighting cock breeds) are grouped into the standing type (Endo et al, 2012 ); the vertical extension of the body trunk by these muscles is the preferred posture in the cock fight. We suggest that the standing posture showing wide chest is also ornamental (Kudo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
“…Researches indicated that the sterna of mammals were segmented and small ( Weaver et al., 2014 ; Eydt et al., 2015 ; Ateşoğlu et al., 2018 ), whereas avian sterna were unsegmented, generally keeled, and highly developed as the largest single bone ( John et al., 2014 ; Zheng et al., 2014 ). This may be because avian sterna made much greater contributions to the operation of the ventilatory apparatus ( Claessens, 2009 ) and the attachment of the massive pectoral muscles ( Kudo et al., 2016 ). The sterna of different birds showed high morphological diversity.…”
Section: Introductionmentioning
confidence: 99%